Adsorption of Mercury on Activated Carbon in Simulated Flue Gas with Continuous Components Change - Hu, Chang-Xing; Zhou, Jin-Song; Li, Jian-Xin; Wang, Yong-Chuan; Zheng, Jiao; Xu, Mei-Juan; Luo, Zhong-Yang; Cen, Ke-Fa (Asian Journal of Chemistry, 2013)
This paper focused on the influence of flue gas component change on elemental mercury (Hg0) adsorption by powder activated carbon from apricot’s shell and discussed the Hg0 adsorption characteristics and mechanism of activated carbon. Experimental results showed that activated carbon from apricot’s shell had no Hg0 adsorption ability in the non-oxidizing atmosphere, such as N2, N2 + CO2 etc. Though the influence on homogeneous oxidation reaction of Hg0 was limited, NO2 was the key factor on heterogeneous catalytic oxidation reaction of Hg0 on the surface of activated carbon. It was easy to form NO2 by reaction between the NO and O2. It could also enhance the Hg0 adsorption ability of activated carbon through preloading NO2 on the surface. Based on these experimental results, it finely proved that Hg0 adsorption by activated carbon was a heterogeneous catalytic oxidation reaction.